Industry 4.0 Driven Green Supply Chain Management in Renewable Energy Sector: A Critical Systematic Literature Review - Muhammad Jameel Labaran; Tariq Masood (Energies, 2023)
This paper is aimed at systematically reviewing the literature on the interface of Green Supply Chain Management (GSCM), Industry 4.0 and renewable energy. The aims of this review are to ascertain current state of the art in GSCM practices, to critically examine the role of industry 4.0 technologies in GSCM adoption, to examine sustainability and supply chain issues within the renewable energy sector, and to critically discuss tackling these issues using industry 4.0 driven GSCM. A total of 215 review and empirical papers from 2004 to 2023 gathered from three databases (ScienceDirect, Scopus and Web of Science) were reviewed. This research found several GSCM practices and succinctly categorized those based on their respective positions along any given value chain. The practices were categorized as related to: procurement and sourcing, product design, corporate relationship, organizational structure/strategy, logistics and transportation, waste and pollution management and manufacturing. We have found that the ten most mentioned GSCM practices are: Green purchasing, Eco-design, Cooperation with customers, Internal Environmental Management, Reverse logistics, Investment recovery, Green manufacturing, Green design, Collaboration with suppliers and Remanufacturing. Various Industry 4.0 technologies including blockchain, Internet of Things, Big Data and Artificial Intelligence were identified and their role in successful GSCM implementation is highlighted. Sustainability and supply chain related challenges within the renewable energy supply chain were found that include material sourcing and end-of-life management challenges. Finally, a perspective is given on the role of Industry 4.0 driven GSCM in tackling the renewable energy supply chain and sustainability challenges. This article concludes with a presentation of managerial implications and future research directions for managers within different sectors, especially the renewable energy industry.